Odnos staršev do športnih dejavnosti predšolskih otrok v Sloveniji ter Bosni in Hercegovini - Rizvić, Sara (Šport (Ljubljana), 2023)
The purpose of the research was to determine whether there are differences in the opinions of parents in Bosnia and Herzegovina and Slovenia about sports activities in preschool age and to find out the differences in their children‘s involvement in additional forms of sports activities. We also wanted to get some information about why they involve their child in a sporting activity and parents‘ opinions about the role they play in their child‘s participation in sports. 701 parents who completely filled out the questionnaire participated in the research. Among them were 213 men (30.4 %) and 488 women (69.6 %). Their children are, on average, 4 years old. Approximately half of the respondents come from Slovenia (49.4 %), and half from Bosnia and Herzegovina (50.6 %). We sent the questionnaire in electronic form to kindergartens in Bosnia and Herzegovina and Slovenia. The obtained data was processed with the SPSS computer program, we used the Hi2 test to test the hypotheses. Statistical significance was determined based on a statistical risk of 5 %. In the comparison between these two countries, we found that Slovenian parents agreed to a statistically significantly higher extent with all statements about the positive impact of sports activities on their child than Bosnian parents and that Slovenian parents more often include their children in additional forms of sports. We also found that parents with a higher level of education statistically significantly more often include their children in additional forms of sports activities than parents with a lower level of education. Slovenian parents are more often active in sports and have higher education than Bosnian parents.
Keywords: Bosna in Hercegovina; otroški vrtec; predšolski otroci; Slovenija; starši; šport; športne dejavnosti